Erratum to: Implementing 360° Quantified Self for childhood obesity: feasibility study and experiences from a weight loss camp in Qatar - Luis Fernandez-Luque (3572423) (2017)
Erratum to: Implementing 360° Quantified Self for childhood obesity: feasibility study and experiences from a weight loss camp in Qatar: https://dx.doi.org/10.1186/s12911-017-0432-6, published online 13 April 2017. Upon publication of the original article [1], the incorrect figure was included as Fig. 8. Additionally, the following paragraph found in Results, under the subheading; Weekend clubs: social media- instagram “The number of photos acquired was 937 in total, but the top 3 contributors (1 girl and 2 boys) uploaded 70% of the photos, as shown in Fig. 8” should read “ The number of photos acquired was 937 in total, but the top 3 contributors (1 girl and 2 boys) uploaded almost 70% of the photos, as shown in Fig. 8” This is to reflect that the actual percentage of 66.5% was rounded to 70%. Other Information Published in: BMC Medical Informatics and Decision Making License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1186/s12911-017-0457-x